2020
DOI: 10.1111/1744-9987.13567
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of plasma and its components and the clinical implications of different methods of apheresis: A narrative review

Abstract: Nowadays, therapeutic plasmapheresis (TP) is accepted as part of the treatment for specific groups of diseases. The availability of different methods, including double filtration and adsorption, increases selectivity for the removal of substances. However, the use of these techniques requires a thorough understanding of the characteristics and components of plasma. By considering pivotal papers from several databases, the aim of this narrative review is to describe the characteristics of plasma related to aphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
(157 reference statements)
0
6
0
Order By: Relevance
“…Patients undergoing TPE have a high rate of iron deficiency anemia; one study found that 60% of patients developed iron deficiency anemia, and 100% of patients had decreased serum iron [ 71 ]. This may be due to use of citrate as an anticoagulant, or due to simple removal of plasma, which contains transferrin, and replacement with an albumin solution [ 72 ]. Other components of plasma may be removed or diluted as well, but iron may be the critical element here.…”
Section: Heterochronic Blood Exchange Plasma Dilution and Blood Donationmentioning
confidence: 99%
“…Patients undergoing TPE have a high rate of iron deficiency anemia; one study found that 60% of patients developed iron deficiency anemia, and 100% of patients had decreased serum iron [ 71 ]. This may be due to use of citrate as an anticoagulant, or due to simple removal of plasma, which contains transferrin, and replacement with an albumin solution [ 72 ]. Other components of plasma may be removed or diluted as well, but iron may be the critical element here.…”
Section: Heterochronic Blood Exchange Plasma Dilution and Blood Donationmentioning
confidence: 99%
“…Time to setup and *prime,minutes 11 11 23-40 11,12 Procedure time*,minutes 91-120 [11][12][13] 133-160 [11][12][13] Time to exchange 1lit of plasma *minutes 25-3311-13 36-37 [11][12][13] PRE% 80-93 11,[13][14][15][16][17] 27-53 10,11,13 Lnlet/blood flow rate,ml/min 5-140 2,11,12,[14][15][16][17] (<5 can be used for small patients) 50-100 7,11,12,15 (depending on filter type used)…”
Section: Atrribute Ctpe(spectral Optia System) Mtpe Systemmentioning
confidence: 99%
“…( 9) Modern treatment approaches are multi model, including emerging molecular and targeted therapies(10) therapeautic Plasma Exchange [TPE] is one such way plasma replacement therapy has been in development for more than 50 years and has become a common and relatively safe treatment (11,12). TPE is a blood component aphersis technology used mainly for symptomatic treatment ; it is used to remove pathological plasma while supplementing a certain amount of normal plasma or solution to treat patients with cancer and related complications (13). TPE can eliminate macromolecules proteins and antibodies, and its precisely because of this immunological property that it is useful in the treatment of patients with malignant tumors (14).…”
Section: Introductionmentioning
confidence: 99%
“…TPE is a blood component apheresis technology used mainly for symptomatic treatment; it is used to remove pathological plasma while supplementing a certain amount of normal plasma or solution to treat patients with cancer and related complications. 7 TPE can eliminate macromolecular proteins and antibodies, and it is precisely because of this immunological property that it is useful in the treatment of patients with malignant tumors. 8 TPE therapy plays an important role in the treatment of a variety of tumors, such as multiple myeloma and Waldenström macroglobulinemia, and can also be used to eliminate paraneoplastic syndromes and excessive levels of chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%